Creative Problem Solving in Small Groups: The Effects of Creativity Training on Idea Generation, Solution Creativity, and Leadership Effectiveness. (24th September 2018) - Puccio, Gerard J.; Burnett, Cyndi; Acar, Selcuk; Yudess, Jo A.; Holinger, Molly; Cabra, John F.
Abstract: This investigation evaluated the degree to which creativity training, idea generation instruction, and creative process impacted idea production, creativeness of solutions, and leadership effectiveness. Three sets of hypotheses were tested with a 114 groups of adults. First, groups whose members had some (i.e., one CPS course) or advanced training (i.e., graduate‐level study in creativity or creativity professionals) were significantly more effective at idea generation than groups without training. Furthermore, leaders with some and advanced training were perceived to be significantly more effective than those with no creativity training. With respect to creativeness of solutions, the advanced training groups outperformed all others. The second set of hypotheses focused on the effectiveness of idea generation instruction (i.e., instructions without brainstorming, brainstorming, and brainstorming with criticism). Analysis revealed no significant difference for idea generation instruction relative to idea production or creativeness of solutions. The final set of hypotheses examined the use of a simple process structure for groups without prior creativity training (i.e., distinct phases for idea generation and solution development). Analysis revealed that those meetings that followed a simple process structure out performed groups that did not follow a process for both idea generation and creativeness of solutions. Further results are presented and implications discussed.